Adicción a dispositivos móviles y ansiedad en adolescentes. - Muñoz Lucio, Erika Brigitt (2025)
Mobile device addiction has emerged as a significant mental health concern, profoundly impacting adolescents' well-being and raising alarms about its association with anxiety and the development of anxiety disorders. This study aims to analyze the relationship between mobile device addiction and anxiety in adolescents. Employing a descriptive- level documentary research design, the study initially reviewed 949 scientific articles from globally recognized databases such as Scopus, PubMed, Web of Science, and Google Scholar, covering the period from 2015 to 2025. Following the application of selection criteria and methodological evaluation using the Critical Review Form for Quantitative Studies (CRF-QS), the final analysis comprised 20 articles pertinent to the variables of interest. The primary findings indicate that adolescents exhibiting high levels of mobile device addiction are at an increased risk of developing anxiety and various anxiety disorders compared to their peers with moderate or low usage. Conditions such as generalized anxiety disorder, social phobia, and separation anxiety are significantly associated with excessive mobile device use. Moreover, factors like nomophobia, fear of missing out (FoMO), and social pressure contribute to heightened technological dependence and the manifestation of anxiety symptoms.